2020
DOI: 10.13189/saj.2020.080503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Training on Speed and Agility among Recreational Football Players

Abstract: Plyometrics are exercises that involved the enhancement of muscle performance. The objective of this study is to evaluate the effects of 6-weeks plyometric training on speed and agility performance among recreational football players. This study was conducted following the pre-post test model of quasi-experimental method. Twenty-two recreational football players were chosen for this study (aged between 19 to 26 years old) and randomly assigned into control (N=11) and intervention group (N=11) for six weeks. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Pratama et al, (2018)stated that there was a significant effect of ladder drills and jump rope exercises on increasing speed, agility, and leg muscle strength. In addition, speed training can be performed with plyometric training, as a study found a significant increase in the difference in sprint time before and after six weeks of plyometric training (t = 3.76, p = 0.001), (Bin Shamshuddin et al, 2020). Therefore, it can be recommended to new members of the student regiment do ladder drills or plyometric exercises to increase speed.…”
Section: Resultsmentioning
confidence: 99%
“…Pratama et al, (2018)stated that there was a significant effect of ladder drills and jump rope exercises on increasing speed, agility, and leg muscle strength. In addition, speed training can be performed with plyometric training, as a study found a significant increase in the difference in sprint time before and after six weeks of plyometric training (t = 3.76, p = 0.001), (Bin Shamshuddin et al, 2020). Therefore, it can be recommended to new members of the student regiment do ladder drills or plyometric exercises to increase speed.…”
Section: Resultsmentioning
confidence: 99%
“…Ability to perform running over a short distance at maximal speed is an indispensable component in soccer performance [21,22]. It is the most frequent action before goal scoring for both scoring and assisting the other player to score [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The time to complete each test is measured in seconds. The Agility t-test was highly reliable with intraclass reliability was 0.98 [3].…”
Section: Instrumentmentioning
confidence: 92%